Radiation-Induced Malignant Peripheral Nerve Sheath Tumor of the Vagus Nerve Following Radiation Treatment of Cervical Paraganglioma - Gregory P. Lekovic (Journal of Neurological Surgery Reports, 2020)
Radiation-induced sarcoma is a known but rare complication of radiation treatment for skull base paraganglioma. We present the cases of a female patient with multiple paraganglioma syndrome treated with external beam radiation treatment who presented 4 years later with a malignant peripheral nerve sheath tumor of the vagus nerve.